Early myocardial damage assessment in dystrophinopathies using 99Tcm-MIBI gated myocardial perfusion imaging - Zhang L; Liu Z; Hu KY; Tian QB; Wei LG; Zhao Z; Shen HR; Hu J (Dove Medical Press, 2015)
Li Zhang,1,* Zhe Liu,2,* Ke-You Hu,3 Qing-Bao Tian,3 Ling-Ge Wei,4 Zhe Zhao,5 Hong-Rui Shen,5 Jing Hu5 1Department of Cardiovascular Disorders, 2Department of Geriatrics, The Third Hospital of Hebei Medical University, 3The Public Health Department, Hebei Medical University, 4Department of Nuclear Medicine, 5Department of Neuromuscular Disorders, The Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China *Li Zhang and Zhe Liu are first coauthors of this paper Background: Early detection of muscular dystrophy (MD)-associated cardiomyopathy is important because early medical treatment may slow cardiac remodeling and attenuate symptoms of cardiac dysfunction; however, no sensitive and standard diagnostic method for MD at an earlier stage has been well-recognized. Thus, the aim of this study was to test the early diagnostic value of technetium 99m-methoxyisobutylisonitrile (99Tcm-MIBI) gated myocardial perfusion imaging (G-MPI) for MD.Methods and results: Ninety-one patients underwent 99Tcm-MIBI G-MPI examinations when they were diagnosed with Duchenne muscular dystrophy (DMD) (n=77) or Becker muscular dystrophy (BMD; n=14). 99Tcm-MIBI G-MPI examinations were repeated in 43 DMD patients who received steroid treatments for 2 years as a follow-up examination. Myocardial defects were observed in nearly every segment of the left ventricular wall in both DMD and BMD patients compared with controls, especially in the inferior walls and the apices by using 99Tcm-MIBI G-MPI. Cardiac wall movement impairment significantly correlated with age in the DMD and BMD groups (rs=0.534 [P<0.05] and rs=0.784 [P<0.05], respectively). Intermittent intravenous doses of glucocorticoids and continuation with oral steroid treatments significantly improved myocardial function in DMD patients (P<0.05), but not in BMD patients.Conclusion: 99Tcm-MIBI G-MPI is a sensitive and safe approach for early evaluation of cardiomyopathy in patients with DMD or BMD, and can serve as a candidate method for the evaluation of progression, prognosis, and assessment of the effect of glucocorticoid treatment in these patients. Keywords: Duchenne muscular dystrophy, Becker muscular dystrophy, dystrophinopathy, 99Tcm-MIBI, cardiomyopathy